EFEKTIVITAS KERASIONALAN PEMBERIAN ANTIDIABETIK PENGOBATAN ORAL PASIEN DIABETES MELLITUS PADA USIA 30-50 TAHUN TIPE 2 DI RAWAT INAP PENYAKIT DALAM RSUD DELI SERDANG LUBUK PAKAM TAHUN 2020 - Sebayang, Loraetta Brety; Anna Teresia Marbun, Romauli; Kartika, Dewi (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Background: Diabetes Mellitus is a chronic condition, which occurs because the body cannot produce insulin, normally or insulin cannot work effectively. Objective: To determine the effectiveness of the rational administration of antidiabetic, oral treatment of diabetes mellitus patients at the age of 30-50 years type 2 in Deli Serdang Hospital, lubuk pakam in 2020. Method: This study is a non-experimental type of research using descriptive methods. Results: Shows that from 72 samples of Type II Diabetes Mellitus patients at Deli Serdang General Hospital, April-July Period 2020. With the number (52.8%) of male sex patients and the number (47.2%) of type patients female genitalia and antidiabetic drugs most widely used by patients, in the period of April-July 2020, namely (20.8%) glycionion + metformin and (20.8%) insulin drugs. the use of DM drugs with the right rational indication (65.3%), Rational with the right medicine (100%), rational with the right dosage (100%), the right rational patient (100%) and the rational way of administration (100:%). Conclusion: Evaluation of drug use is a structured quality assurance process that is carried out continuously to ensure that the drugs used are appropriate, safe, and efficient.